Grain Size and Macrosegregation Control of Large-Sized AA2219 Billets by Internal Electromagnetic Stirring in DC Casting - Haodong Zhao; Haodong Zhao; Haodong Zhao; Zhifeng Zhang; Zhifeng Zhang; Zhifeng Zhang; Bao Li; Bao Li; Bao Li; Yuelong Bai; Yuelong Bai; Yuelong Bai; et al. (Frontiers in Materials, 2022)
This work focuses on the effect of internal electromagnetic stirring (IEMS) on grain size and macrosegregation in direct-chill (DC) casting of an AA2219 billet with a diameter of 880 mm. The IEMS process has been applied to provide forced convection within the solidifying melt to achieve an efficient reduction of mean grain size and alleviate the formation of macrosegregation. Two casting electromagnetic parameters (the stirring electric current and frequency) of the IEMS process were applied to assess the uniformity of the microstructure and macrosegregation of the billet. The experimental results show that finer and more uniform grains in the billet prepared by the IEMS process than those of traditional DC casting have been observed. The IEMS process has a great influence on the improvement of the macrosegregation, but the greater electromagnetic field would result in worse macrosegregation in the center of the billet.